Assessment of heart rate turbulence in dogs with myxomatous mitral valve disease - Julio P. dos Santos (Tripoli University, 2021)
Background: Myxomatous mitral valve degeneration (MMVD) is the most common heart disease affecting small dogs, it reduces cardiac output resulting in compensatory adaptation of the autonomic nervous system. Chronically it leads to reduced heart rate variability (HRV) which is an accurate marker for autonomic balance. More than two decades ago in human medicine an indicator of autonomic balance that happens after a premature ventricular beat, it was described as heart rate turbulence (HRT). In humans with ischaemic heart disease the absence of HRT has proven to be a more accurate and an independent indicator of mortality than known HRV parameters. Currently there are very few studies of HRT in dogs and it is still not tested in small dogs within different stages of myxomatous mitral valve disease. Aim: The aim of this study was to assess the HRT indicators, onset and slope, in small dogs with myxomatous mitral valve disease and to statistically test it. Methods: Dogs under 25 kg had electrocardiogram and echocardiography performed and, in some patients, holter monitoring was carried out. Data was divided into groups B1, B2, C and D for mean comparison with ANOVA and Tukey test. In addition, Receiver Operating Characteristic (ROC) curve for differentiating among symptomatic and asymptomatic dogs and for differentiating between remodeled and non-remodeled hearts. The Pearson was executed after correlations of TO and TS with commonly used echocardiographic parameters. Results: Variance analyses held significant differences in TO and TS between stages B1 from stages C and D, while B2 held similarity to the other groups. In the Receiver Operating Curve(ROC) was found a very good AUC for differentiating among symptomatic and asymptomatic dogs and remodeled and non-remodeled dogs. Few echocardiography parameters held weak correlation with TO while others held weak to moderate correlation with TS. Conclusion: In dogs with MMVD and without other diseases, heart rate turbulence is a feasible indicator for autonomic balance. Our result suggests HRT changes as the MMVD progresses and CHF is present. More studies with HRT are needed. The number of VPCs may be the strongest limitation for the technique.